Sexual Victimization of Youth With a Physical Disability: An Examination of Prevalence Rates, and Risk and Protective Factors. (November 2014) - Mueller-Johnson, Katrin; Eisner, Manuel P.; Obsuth, Ingrid
Children with disabilities have been shown to be at greater risk of victimization than those without. Although much of the research combines disability of any type into a single disability category, recent evidence suggests that not all types of disabilities are equally associated with victimization. To date, little knowledge exists about the victimization of youth with physical disabilities. This study used data from a national school-based survey of adolescents ( n = 6, 749, mean age = 15.41, SD = .66) in Switzerland to investigate sexual victimization (SV) among physically disabled youth. Two subtypes of SV were differentiated: contact SV, including penetration or touching/kissing, and non-contact SV, such as exhibitionism, verbal harassment, exposure to sexual acts, or cyber SV. A total of 360 (5.1%) youth self-identified as having a physical disability. Lifetime prevalence rates for contact SV were 25.95% for girls with a physical disability (odds ratio [OR] = 1.29 compared with able-bodied girls), 18.50% for boys with physical disability (OR = 2.78 compared with able-bodied boys), and 22.35% for the total sample with physical disability (OR = 1.74 compared with able-bodied youth). For non-contact SV, the lifetime prevalence was 48.11% for girls with a physical disability (OR = 1.44 compared with able-bodied girls), 31.76% for boys with physical disability (OR = 1.95 compared with able-bodied boys), and 40.28% for the total sample with physical disability (OR = 1.67 compared with able-bodied youth). After controlling for other risk factors, physical disability was a significant predictor of contact and non-contact SV for boys, but not for girls.